A conceptual model to find the effectiveness of Islamic advertising - Haque, A. K. M. Ahasanul (2014)
With the “unholy trinity” on the loose, perhaps it is high time to devise and implement advertisements that cater to the ethical standards. Overview of the literature finds a grave dearth of empirical researches pertaining to Islamic advertising, despite its proposed imminent need. This paper proposes a conceptual model to evaluate the effectiveness of Islamic advertising. Taking a typical model of how advertising impacts consumer response as the platform, this research proposes a model for how Islamic advertising would affect the same. In measuring this effect, religiosity and attitude-towards-advertising-in-general are taken as the moderating variables. The role of culture cannot be undermined in any such study. Here, it surrounds the overall model. This conceptual model can help in empirically finding the effectiveness of Islamic advertising. Such a model, if proved effective, would not only benefit the Muslim world, but can revolutionize the advertising practices. (word count:144 words) Keywords: Islamic advertising, Islamic marketing, religiosity, attitude-towards-advertising-in-general.